ANSWER
C. 23
Step-by-step explanation
We are given that Z is the midpoint of AC and Y is the midpoint of BC.
According to the midpoint theorem of triangles, the midsegment of a triangle (YZ) is equal to half the length of side parallel to it (AB)
This means that:
![YZ\text{ = }(1)/(2)AB](https://img.qammunity.org/2023/formulas/mathematics/college/zdynyx1lg8sbelx96aokgzd810s86ze9ah.png)
So, we have that:
![\begin{gathered} 21\text{ = }(1)/(2)(2x\text{ - 4)} \\ 21\text{ = x - 2} \\ \text{Collect like terms:} \\ \Rightarrow\text{ x = 21 + 2} \\ \text{x = 23} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/if9igk87vf4npttorve2v1q6e58pty2dqe.png)
The answer is Option C.